THE IMPACT OF COGNITIVE IMPAIRMENT AFTER STROKE ON QUALITY OF LIFE AND DAILY LIFE ACTIVITIES - Fasihah Irfani Fitri, Aida Fithrie & Aldy S Rambe (International Journal of Research Science and Management, 2020)
Stroke is a major cause of death and disability worldwide. Cognitive impairment is commonly seen after stroke and might significantly affect the functional outcome. The study aimed to investigate the impact of cognitive impairment after stroke on quality of life and daily life activities. This was a cross-sectional study involving 38 post stroke patients, consisted of 23 males (60.5%) and 15 females (39.5%). All patients underwent neuropsychology examination and assessment of quality of life and activity daily living. The proportion of poststroke cognitive impairment was 44.7%. Cognitive impairment after stroke affects several domains, including attention, memory, executive function and visuospatial. Cognitive impairment was significantly associated with worse performance in daily life activities